Epiphytic bacterial community composition on four submerged macrophytes in different regions of Taihu Lake - Fang, Hongda; Zhen, Zhuo; Yang, Fan; Su, Hailei; Wei, Yuan (Frontiers in Plant Science, 2024)
The epiphytic bacteria in aquatic ecosystems, inhabiting a unique ecological niche with significant ecological function, have long been the subject of attention. Habitat characteristics and plant species are believed to be important in controlling the assembly of epiphytic bacteria. However, the underlying principle governing the assembly of the epiphytic bacterial community on macrophytes is far from clear. In this study, we systematically compared the diversity and community composition of epiphytic bacteria both in different habitats and on different species of macrophytes where they were attached. Results suggested that neither the plant species nor the habitat had a significant effect on the diversity and community of epiphytic bacteria independently, indicating that the epiphytic bacterial community composition was correlated to both geographical distance and individual species of macrophytes. Furthermore, almost all of the abundant taxa were shared between different lake regions or macrophyte species, and the most abundant bacteria belonged to Proteobacteria and Firmicutes. Our results demonstrated that the competitive lottery model may explain the pattern of epiphytic bacterial colonization of submerged macrophyte surfaces. This research could provide a new perspective for exploring plant–microbe interaction in aquatic systems and new evidence for the lottery model as the mechanism best explaining the assembly of epiphytic bacteria.